Entrepreneurial Ecosystem and Regional Competitive Advantage: A Case Study on the Creative Economy of Indonesia - Purbasari, Ratih; Wijaya, Chandra; Rahayu, Ning (Advances in Social Sciences Research Journal, 2019)
This investigation employs Indonesia’s creative economy sector as a case study to discover how an entrepreneurial ecosystem promotes competitive advantage (CA) and to ascertain the elements involved within the entrepreneurial ecosystem and their functions. Each actor’s role in encouraging CA in Indonesia’s creative economy is explained, analyzed, and deduced. The results reveal that entrepreneurship and culture are the major contributors to CA. The government’s regulations and policies supporting entrepreneurial activities are also pivotal although access to markets still need to be built. Finally, this paper states the implications of this study for scholars and practitioners and provides future research directions.